Photopolymerization initiator comprising aryl iodonium salt for dental photocurable composition
By using specific structures of cesium iodide salts as photocuring in dental photocuring compositions as photocuring initiator, combined with photosensitizers and accelerators, the shortcomings in the physical properties and ambient light stability of the photocuring initiator in the prior art are solved, and high-efficiency photocuring and good mechanical properties are achieved.
Patent Information
- Application Number
- JP2025006585
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-03-16
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing dental photocuring initiator cannot obtain sufficient physical properties in photocuring dental photocuring compositions, and its stability to ambient light is poor, affecting the operating time and long-term stability of dental restoration materials.
The use of specific structures of aryliodonium salt as the photocuring initiator, combined with photosensitizer and accelerator, improves the solubility and photocuring activity of the initiator in dental photocuring compositions and reduces the sensitivity to ambient light.
The photocuring sensitivity and ambient light stability of the dental photocuring composition are improved, sufficient photocuring time and good mechanical properties, such as bending intensity, avoiding the problem of increasing viscosity during photocuring.
Smart Images

Figure 2025061420000001 
Figure 2025061420000002 
Figure 2025061420000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental photocurable composition and a photopolymerization initiator for use in the dental photocurable composition. [Background technology]
[0002] In the dental field, dental photocurable compositions are used for treatment of the oral cavity, and are applied to dental adhesives, dental composite resins, dental core construction materials, dental resin cements, dental surface coating materials, dental pit and fissure sealants, dental manicure materials, etc. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4093974 [Patent Document 2] Patent No. 4596786 Summary of the Invention [Problem to be solved by the invention]
[0004] However, sufficient physical properties could not be obtained with the photopolymerization initiators used in dental photocurable compositions.
[0005] Patent Documents 1 and 2 propose a photopolymerization initiator comprising a photoacid generator (a triazine compound or a specific aryl iodonium salt), a sensitizer and an electron donor compound, but they fail to provide sufficient physical properties.
[0006] There is a demand for a photopolymerization initiator that exhibits excellent sensitivity to photopolymerization and can ensure a sufficient pot life against environmental light, and an object of the present invention is to provide a dental photocurable composition containing the photopolymerization initiator. [Means for solving the problem]
[0007] The present invention relates to a photopolymerization initiator (c) used in a dental photocurable composition, (c-1) a photosensitizer, (c-2) a polymerization accelerator, and (c-3) a compound represented by the formula (1):
[0008] [ka] (wherein R1 represents an organic group bonded to I, R2 represents an alkyl group in which some of the hydrogen atoms are substituted with fluorine atoms, and b represents the number of alkyl groups and is an integer of 1 to 5). It is a photopolymerization initiator comprising: Effect of the Invention
[0009] The photopolymerization initiator of the present invention makes it possible to obtain a dental photocurable composition that exhibits excellent sensitivity to irradiated light and ensures a sufficient pot life against ambient light. In addition, the dental photocurable composition containing the photopolymerization initiator of the present invention has excellent bending strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the (c) photopolymerization initiator of the present invention, (c-3) of formula (1) may be an aryl iodonium salt in which R2 is an alkyl group in which 80% or more of the hydrogen atoms are substituted with fluorine atoms.
[0011] The dental photocurable composition may include the photopolymerization initiator (c) and the polymerizable monomer (a). The dental photocurable composition may include the photopolymerization initiator (c), the polymerizable monomer (a), and the filler (b).
[0012] The dental photocurable composition may contain, relative to 100 parts by mass of the polymerizable monomer (a), a photopolymerization initiator (c) of 0.1 to 5 parts by mass of a photosensitizer (c-1), 0.01 to 10 parts by mass of a polymerization accelerator (c-2), and 0.01 to 10 parts by mass of an aryl iodonium salt represented by formula (1) (c-3). The dental photocurable composition may contain 10 to 1900 parts by weight of the filler (b) relative to 100 parts by weight of the polymerizable monomer (a).
[0013] The dental photocurable composition may be a dental adhesive, a dental composite resin, a dental core building material, a dental resin cement, a dental surface coating material, a dental pit and fissure sealant, or a dental manicure material.
[0014] Each component of the dental photocurable composition of the present invention will be described in detail below. The present invention relates to a photopolymerization initiator and a dental photocurable composition containing the photopolymerization initiator. The dental photocurable composition of the present invention is used as a dental adhesive, a dental composite resin, a dental core material, a dental resin cement, a dental surface coating material, a dental pit and fissure sealant, and a dental manicure material.
[0015] In dental clinical practice, in order to restore the aesthetics and functions of teeth that have been lost due to caries or fractures, treatments are performed using direct restoration with dental composite resins after pretreatment with dental adhesives, or indirect restoration in which a prosthetic device made of ceramics or hard resin is attached using dental resin cement. Dental composite resins and dental resin cements are prepared by mixing a resin matrix made of several types of polymerizable monomers, various fillers such as inorganic fillers and organic-inorganic composite fillers, and a polymerization initiator to form a uniform paste. Dental filling composite resins are filled into teeth in an uncured paste state, and are given the anatomical form of natural teeth with dental instruments and other dental tools, and then hardened by irradiation with light from a dental light irradiator or the like. The light irradiated from the light irradiator generally has a light intensity of 100 to 2000 mW / cm in the wavelength range of about 360 to 500 nm. 2 On the other hand, dental resin cement is used when bonding a prosthesis to a cavity or an abutment tooth, and is hardened by irradiating the prosthesis with light after the prosthesis is attached to the cavity or the abutment tooth.
[0016] As a photopolymerization initiator for dental composite resins and dental resin cements, a photosensitizer or a system in which a photosensitizer is combined with a suitable photopolymerization accelerator is widely used. As a photosensitizer, an acylphosphine oxide compound or an α-diketone compound is known, and in particular, an α-diketone compound has a polymerization initiation ability in the wavelength range of visible light that has little effect on the human body. In addition, as a polymerization accelerator to be combined with a photosensitizer, a tertiary amine compound is well known, and a combination of an α-diketone compound and a tertiary amine compound has high polymerization activity against irradiated light, and is therefore used in the field of dental materials. A dental photocurable composition containing the photopolymerization initiator exhibits excellent mechanical properties such as hardness, bending strength, and compressive strength required for dental filling composite resins and dental resin cements.
[0017] However, when the combination of the above-mentioned α-diketone compound and tertiary amine compound is used as a photopolymerization initiator, the problem of poor environmental light stability arises. In other words, the procedure is performed under white light (ambient light) such as a dental light that the surgeon uses to illuminate the oral cavity or an indoor light such as a fluorescent lamp, but when only the combination of the above-mentioned α-diketone compound and tertiary amine compound is used as a photopolymerization initiator, it shows high sensitivity not only to the irradiated light but also to the ambient light, so that during operations such as filling, building up, and fitting, the hardening gradually progresses, and the viscosity of the paste increases, making the operation difficult.
[0018] In order to solve the above problems, if the amount of photopolymerization initiator added is reduced or the amount of polymerization inhibitor added is increased, the stability against environmental light is improved, but the sensitivity to irradiation light is also reduced at the same time. Therefore, even if the irradiation light is irradiated for a long time, sufficient curing does not proceed, and the mechanical strength of the cured body is reduced, or a large amount of unpolymerized surface layer remains, causing problems such as coloring over time in the oral cavity. Another problem is that when a tertiary amine compound is blended as a polymerization accelerator, the cured body is easily discolored when exposed to sunlight, etc. When used as a dental adhesive, the adhesive strength decreases when a thermal load equivalent to that in the oral cavity is applied, and the adhesive layer after curing discolors. Thus, it was difficult to achieve both characteristics, such as environmental light stability and high polymerization activity against irradiation light.
[0019] As a photopolymerization initiator, a photopolymerization initiator containing a specific aryliodonium salt, a sensitizer, and an electron donor compound has been proposed, but sufficient physical properties could not be obtained. Photopolymerization initiators containing aryliodonium salts have the following problems. First, conventional aryliodonium salts have low solubility in polymerizable monomers, and are limited to being mixed at extremely low concentrations due to the risk of precipitation, etc., assuming the temperature of clinical use. Therefore, the photopolymerization activity is insufficient. Furthermore, by using aryliodonium salts in combination with polymerization accelerators such as tertiary amine compounds, the photosensitivity increases, so the stability to environmental light is low, the operable time is significantly shortened, and the discoloration of the cured body when exposed to sunlight, etc. is further accelerated. Although the detailed mechanism by which the discoloration occurs is unknown, it is speculated that the discoloration is promoted by the cationic moiety contained in the structure of the photoacid generator and the polymerization accelerator, such as a tertiary amine compound or an organometallic compound, forming a salt or interacting with each other.
[0020] However, through the investigations of the present inventors, it was discovered that when a photopolymerization initiator containing an aryl iodonium salt having a specific structure is used in a dental photocurable composition, the solubility in the polymerizable monomer is improved, there is no risk of precipitation, etc., appropriate photosensitivity is exhibited, and discoloration when exposed to sunlight, etc. is significantly reduced, which led to the completion of the present invention.
[0021] As described above, the present invention provides a dental photocurable composition that exhibits high polymerization activity when exposed to light, and when applied to, for example, a dental filling composite resin or a dental resin cement, has aesthetic properties and mechanical properties (hardness, flexural strength, compressive strength, etc.), and when applied as an adhesive, has durable adhesive strength, as well as excellent long-term storage stability, environmental light stability, and color stability.
[0022] <(a) Polymerizable monomer> The polymerizable monomer (a) that can be used in the present invention can be any known monofunctional and / or polyfunctional polymerizable monomer that is generally used in the dental field, without any restrictions. A representative example of a polymerizable monomer that is generally preferably used is a (meth)acrylate monomer or a (meth)acryloyl polymerizable monomer having an acryloyl group and / or a methacryloyl group. In the present invention, (meth)acrylate or (meth)acryloyl is used to collectively indicate both an acryloyl group-containing polymerizable monomer and a methacryloyl group-containing polymerizable monomer.
[0023] Specific examples of (meth)acrylate polymerizable monomers that can be used as the (a) polymerizable monomer are as follows: Examples of monofunctional monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate, i-butyl (meth)acrylate), hexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, glycidyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and allyl (meth)acrylate. Examples of the suitable monomer units include (meth)acrylic acid esters such as 2-ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, glycerol (meth)acrylate, and isobornyl (meth)acrylate; silane compounds such as γ-(meth)acryloyloxypropyltrimethoxysilane and γ-(meth)acryloyloxypropyltriethoxysilane; and nitrogen-containing compounds such as 2-(N,N-dimethylamino)ethyl (meth)acrylate, N-methylol (meth)acrylamide, and diacetone (meth)acrylamide.
[0024] Examples of aromatic bifunctional monomers include 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxy phenyl)propane, 2(4-(meth)acryloyloxyethoxyphenyl)-2(4-(meth)acryloyloxydiethoxyphenyl)propane, 2(4-(meth)acryloyloxydiethoxyphenyl)-2(4-(meth)acryloyloxytriethoxyphenyl)propane, 2(4-(meth)acryloyloxydipropoxyphenyl)-2(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, and the like.
[0025] Examples of the aliphatic difunctional monomer include 2-hydroxy-3-acryloyloxypropyl methacrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and glycerol di(meth)acrylate.
[0026] Examples of the trifunctional monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, and pentaerythritol tri(meth)acrylate.
[0027] Examples of the tetrafunctional monomer include pentaerythritol tetra(meth)acrylate and ditrimethylolpropane tetra(meth)acrylate.
[0028] Examples of the urethane-based polymerizable monomer include di(meth)acrylates having a bifunctional or trifunctional or higher urethane bond derived from an adduct of a polymerizable monomer having a hydroxyl group, such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, or 3-chloro-2-hydroxypropyl(meth)acrylate, with a diisocyanate compound, such as methylcyclohexane diisocyanate, methylenebis(4-cyclohexylisocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, diisocyanate methylmethylbenzene, or 4,4-diphenylmethane diisocyanate.
[0029] There is no restriction on the use of oligomers or prepolymers having at least one polymerizable group in the molecule other than these (meth)acrylate polymerizable monomers. In addition, there is no problem even if the same molecule has a substituent such as a fluoro group. The above-described polymerizable monomers can be used alone or in combination of two or more.
[0030] The (a) polymerizable monomer contained in the dental photocurable composition of the present invention may contain a known acidic group-containing polymerizable monomer in order to impart adhesiveness to a tooth structure or a prosthetic device. Specific examples of the acidic group possessed by the acidic group-containing polymerizable monomer include a phosphoric acid group, a pyrophosphoric acid group, a phosphonic acid group, a carboxylic acid group, a sulfonic acid group, a thiophosphoric acid group, etc., and the acidic group-containing polymerizable monomer refers to a polymerizable monomer having at least one of these groups, and is preferably 10-methacryloyloxydecyl dihydrogen phosphate, 6-methacryloxyhexyl phosphonoacetate, or 4-methacryloxyethyl trimellitic acid. From the viewpoint of imparting adhesiveness, the amount of the polymerizable monomer may be 5 to 60 parts by weight, more preferably 10 to 50 parts by weight, out of 100 parts by weight of the total amount of polymerizable monomers in the composition.
[0031] The dental photocurable composition of the present invention may contain a silane coupling agent to impart adhesion to glass ceramics. Any known silane coupling agent may be used without limitation, but 3-methacryloxypropyltrimethoxysilane may also be used. From the viewpoint of imparting adhesion, the compounding amount may be 0.5 to 10 parts by weight, for example, 0.5 to 5 parts by weight, out of 100 parts by weight of the total amount of polymerizable monomers in the composition.
[0032] <(b) Filler> As the (b) filler that can be used in the present invention, any known filler that is generally used in dental composite materials can be used.
[0033] (b) Fillers include inorganic fillers, organic fillers, and organic-inorganic composite fillers, and these can be used alone or in combination regardless of the type of filler.
[0034] The filler is not particularly limited, but examples thereof include silica glass, fluoroaluminosilicate glass, fluoroaluminoborosilicate glass, other silicate glasses, and zirconium silicate glasses including zirconia, and among these, zirconium silicate is preferable.
[0035] The above-mentioned (b) filler can be treated with a surface treatment material, typically a silane coupling material, for the purpose of improving the affinity with the polymerizable monomer, the dispersibility in the polymerizable monomer, and the mechanical strength and water resistance of the cured body. Such a surface treatment material and surface treatment method are not particularly limited, and known methods can be used without limitation. The silane coupling material used for the surface treatment of the filler may be methyltrimethoxysilane, methyltriethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, γ-methacryloyloxypropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, or hexamethyldisilazane. In addition to the silane coupling material, the surface treatment of the filler can be performed by a method using a titanate-based coupling material or an aluminate-based coupling material. The amount of the surface treatment agent in the filler is preferably 0.01 to 30 parts by weight, more preferably 0.5 to 20 parts by weight, based on 100 parts by weight of the filler before treatment.
[0036] The shape of the filler is not particularly limited, and amorphous and spherical fillers can be used. The average particle size of the filler is preferably 0.01 μm to 50 μm, more preferably 0.1 μm to 30 μm, even more preferably 0.5 μm to 20 μm, and even more preferably 0.5 μm to 10 μm.
[0037] The amount of the filler (b) to be blended is preferably 10 to 1900 parts by weight, more preferably 30 to 900 parts by weight, and even more preferably 100 to 900 parts by weight, relative to 100 parts by weight of the polymerizable monomer (a). If the amount blended is more than 1900 parts by weight, the paste property of the composition becomes hard and difficult to handle.
[0038] <(c) Photopolymerization initiator> <(c-1) Photosensitizer> The photosensitizer (c-1) used in the dental photocurable composition of the present invention is not particularly limited, and any known compound generally used in the dental field can be used without any restrictions.
[0039] Specific examples of the photosensitizer include α-diketones such as benzil, camphorquinone, α-naphthyl, acetonaphthene, p,p'-dimethoxybenzyl, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, and naphthoquinone; benzoin alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; thioxanthones such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; benzophenones such as benzophenone, p-chlorobenzophenone, and p-methoxybenzophenone; trimethylbenzoyldiphenylphosphine oxide, acylphosphine oxide such as bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1, ketals such as benzyl dimethyl ketal, benzyl diethyl ketal, benzyl (2-methoxyethyl ketal), titanocenes such as bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]-titanium, bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium, bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-disiloxyphenyl)-titanium, and the like.
[0040] The photosensitizer (c-1) used can be appropriately selected depending on the wavelength, intensity, and light irradiation time of the light used for polymerization, and the types and amounts of other components to be combined. The photosensitizer can be used alone or in combination of two or more kinds. Among them, α-diketone compounds having a maximum absorption wavelength in the visible light region are preferably used, and camphorquinone may be particularly used.
[0041] Usually, the amount of the photosensitizer (c-1) is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 3 parts by weight, and even more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the total amount of the polymerizable monomer (a). If the amount of the photosensitizer is less than 0.01 parts by weight, the polymerization activity to the irradiated light is poor and the curing is insufficient. If the amount is more than 5 parts by weight, the curing property is sufficient, but the environmental light stability is shortened and the yellowness increases.
[0042] <(c-2) Polymerization accelerator> The polymerization accelerator (c-2) used in the dental adhesive composition of the present invention is not particularly limited as long as it has the polymerization accelerator ability, and any known polymerization accelerator generally used in the dental field can be used without any limitation. As the polymerization accelerator, tertiary amine compounds such as aromatic tertiary amine compounds and aliphatic tertiary amine compounds, and organometallic compounds can be used.
[0043] Specific examples of the aromatic tertiary amine compound include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, pN,N-dimethyl-toluidine, mN,N-dimethyl-toluidine, pN,N-diethyl-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid ... Examples of the dimethylaminobenzoic acid ethyl ester, p-dimethylaminobenzoic acid amino ester, N,N-dimethylanthranilic acid methyl ester, N,N-dihydroxyethylaniline, pN,N-dihydroxyethyl-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-xylidine, 4-dimethylaminopyridine, N,N-dimethyl-α-naphthylamine, N,N-dimethyl-β-naphthylamine, etc. Also, for example, pN,N-dimethyl-toluidine or pN,N-dihydroxyethyl-toluidine may be used.
[0044] Specific examples of the aliphatic tertiary amine compound include tributylamine, tripropylamine, triethylamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, 2-(N,N-diisopropylamino)ethyl methacrylate, 2,2'-(n-butylimino)diethanol, N-[3-(dimethylamino)propyl]acrylamide, etc. In addition, it may be, for example, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, or triethanolamine.
[0045] The organometallic compounds include organometallic compounds containing scandium (Sc), titanium (Ti), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), tin (Sn), zinc (Zn), and zirconia (Zr), and are preferably organometallic compounds containing tin (Sn), vanadium (V), and copper (Cu). Specifically, organometallic compounds containing tin (Sn) include dibutyl-tin-diacetate, dibutyl-tin-dimaleate, dioctyl-tin-dimaleate, dioctyl-tin-dilaurate, dibutyl-tin-dilaurate, dioctyl-tin-diversatate, dioctyl-tin-S,S'-bis-isooctylmercaptoacetate, and tetramethyl-1,3-diacetoxydistannoxane, and organometallic compounds containing vanadium (V) include vanadium acetylacetonate, divanadium tetroxide, and the like. Examples of the organometallic compounds containing copper (Cu) include copper acetylacetonate, copper naphthenate, copper octoate, copper acetylacetonate stearate, copper naphthenate, copper octoate, copper stearate, and copper acetate.
[0046] The type of polymerization accelerator (c-2) used can be appropriately selected depending on the types and amounts of other components to be combined. The polymerization accelerator can be used alone or in combination of two or more kinds.
[0047] Usually, the blending amount of the polymerization accelerator (c-2) is preferably 0.01 to 10 parts by weight, more preferably 0.05 to 5 parts by weight, based on 100 parts by weight of the total amount of the polymerizable monomer (a). If the blending amount of the polymerization accelerator is less than 0.01 parts by weight, the polymerization accelerating ability is poor and curing is likely to be insufficient. If the blending amount is more than 10 parts by weight, although sufficient curing ability is obtained, the ambient light stability is shortened and discoloration of the cured body increases.
[0048] <(c-3) Aryl iodonium salts> The aryliodonium salt (c-3) used in the dental adhesive composition of the present invention is an aryliodonium salt represented by formula (1).
[0049] [ka] [(R1)2I] in the formula + The cationic portion of [(R2) b PF 6-b ] - "In the formula, R1 represents an organic group bonded to I, R2 represents an alkyl group in which some of the hydrogen atoms are replaced with fluorine atoms, and b represents the number of alkyl groups, an integer of 1 to 5.
[0050] R1 in formula (1) represents an organic group bonded to I, and R1 may be the same or different. R1 represents an aryl group having 6 to 30 carbon atoms, a heterocyclic group having 4 to 30 carbon atoms, an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, or an alkynyl group having 2 to 30 carbon atoms, which may be substituted with at least one selected from the group consisting of alkyl, hydroxy, alkoxy, alkylcarbonyl, arylcarbonyl, alkoxycarbonyl, aryloxycarbonyl, arylthiocarbonyl, acyloxy, arylthio, alkylthio, aryl, heterocyclic, aryloxy, alkylsulfinyl, arylsulfinyl, alkylsulfonyl, arylsulfonyl, alkyleneoxy, amino, cyano, nitro groups, and halogens.
[0051] In the above, examples of the aryl group having 6 to 30 carbon atoms include monocyclic aryl groups such as a phenyl group, and condensed polycyclic aryl groups such as naphthyl, anthracenyl, phenanthrenyl, pyrenyl, chrysenyl, naphthacenyl, benzanthracenyl, anthraquinolyl, fluorenyl, naphthoquinone, and anthraquinone.
[0052] Examples of the heterocyclic group having 4 to 30 carbon atoms include cyclic groups containing 1 to 3 heteroatoms such as oxygen, nitrogen, and sulfur, which may be the same or different. Specific examples include monocyclic heterocyclic groups such as thienyl, furanyl, pyranyl, pyrrolyl, oxazolyl, thiazolyl, pyridyl, pyrimidyl, and pyrazinyl, and condensed polycyclic heterocyclic groups such as indolyl, benzofuranyl, isobenzofuranyl, benzothienyl, isobenzothienyl, quinolyl, isoquinolyl, quinoxalinyl, quinazolinyl, carbazolyl, acridinyl, phenothiazinyl, phenazinyl, xanthenyl, thianthrenyl, phenoxazinyl, phenoxathiinyl, chromanyl, isochromanyl, dibenzothienyl, xanthonyl, thioxanthonyl, and dibenzofuranyl.
[0053] Examples of the alkyl group having 1 to 30 carbon atoms include linear alkyl groups such as methyl, ethyl, propyl, butyl, hexadecyl, and octadecyl, branched alkyl groups such as isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, tert-pentyl, and isohexyl, and cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl. Examples of the alkenyl group having 2 to 30 carbon atoms include linear or branched groups such as vinyl, allyl, 1-propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, and 1-methyl-1-propenyl. Examples of the alkynyl group having 2 to 30 carbon atoms include linear or branched groups such as ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-methyl-1-propynyl, and 1-methyl-2-propynyl.
[0054] The above-mentioned aryl group having 6 to 30 carbon atoms, heterocyclic group having 4 to 30 carbon atoms, alkyl group having 1 to 30 carbon atoms, alkenyl group having 2 to 30 carbon atoms, or alkynyl group having 2 to 30 carbon atoms may have at least one type of substituent, and examples of the substituent include linear alkyl groups having 1 to 18 carbon atoms such as methyl, ethyl, propyl, butyl, and octadecyl; branched alkyl groups having 1 to 18 carbon atoms such as isopropyl, isobutyl, sec-butyl, and tert-butyl; cycloalkyl groups having 3 to 18 carbon atoms such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl; hydroxy groups; linear or branched alkoxy groups having 1 to 18 carbon atoms such as methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, sec-butoxy, tert-butoxy, and dodecyloxy; Straight-chain or branched alkylcarbonyl groups having 2 to 18 carbon atoms, such as acetyl, propionyl, butanoyl, 2-methylpropionyl, heptanoyl, 2-methylbutanoyl, 3-methylbutanoyl, and octanoyl; arylcarbonyl groups having 7 to 11 carbon atoms, such as benzoyl and naphthoyl; straight-chain or branched alkoxycarbonyl groups having 2 to 19 carbon atoms, such as methoxycarbonyl, ethoxycarbonyl, propoxycarbonyl, isopropoxycarbonyl, butoxycarbonyl, isobutoxycarbonyl, sec-butoxycarbonyl, and tert-butoxycarbonyl; aryloxycarbonyl groups having 7 to 11 carbon atoms, such as phenoxycarbonyl and naphthoxycarbonyl; arylthiocarbonyl groups having 7 to 11 carbon atoms, such as phenylthiocarbonyl and naphthoxythiocarbonyl; linear or branched acyloxy groups having 2 to 19 carbon atoms, such as acetoxy, ethylcarbonyloxy, propylcarbonyloxy, isobutylcarbonyloxy, sec-butylcarbonyloxy, tert-butylcarbonyloxy, and octadecylcarbonyloxy;Arylthio groups having 6 to 20 carbon atoms, such as phenylthio, biphenylylthio, methylphenylthio, chlorophenylthio, bromophenylthio, fluorophenylthio, hydroxyphenylthio, methoxyphenylthio, naphthylthio, 4-[4-(phenylthio)benzoyl]phenylthio, 4-[4-(phenylthio)phenoxy]phenylthio, 4-[4-(phenylthio)phenyl]phenylthio, 4-(phenylthio)phenylthio, 4-benzoylphenylthio, 4-benzoyl-chlorophenylthio, 4-benzoyl-methylthiophenylthio, 4-(methylthiobenzoyl)phenylthio, and 4-(p-tert-butylbenzoyl)phenylthio; linear or branched alkylthio groups having 1 to 18 carbon atoms, such as methylthio, ethylthio, propylthio, tert-butylthio, neopentylthio, and dodecylthio; aryl groups having 6 to 10 carbon atoms, such as phenyl, tolyl, dimethylphenyl, and naphthyl; Heterocyclic groups having 4 to 20 carbon atoms, such as thienyl, furanyl, pyranyl, xanthenyl, chromanyl, isochromanyl, xanthonyl, thioxanthonyl, and dibenzofuranyl; aryloxy groups having 6 to 10 carbon atoms, such as phenoxy and naphthyloxy; linear or branched alkylsulfinyl groups having 1 to 18 carbon atoms, such as methylsulfinyl, ethylsulfinyl, propylsulfinyl, tert-pentylsulfinyl, and octylsulfinyl; arylsulfinyl groups having 6 to 10 carbon atoms, such as phenylsulfinyl, tolylsulfinyl, and naphthylsulfinyl; linear or branched alkylsulfonyl groups having 1 to 18 carbon atoms, such as methylsulfonyl, ethylsulfonyl, propylsulfonyl, isopropylsulfonyl, butylsulfonyl, and octylsulfonyl; arylsulfonyl groups having 6 to 10 carbon atoms, such as phenylsulfonyl, tolylsulfonyl (tosyl group), and naphthylsulfonyl; alkyleneoxy groups; cyano groups; Nitro groups; halogens such as fluorine, chlorine, bromine, and iodine;
[0055] In formula (1), R2 represents an alkyl group substituted with a fluorine atom, and may have 1 to 4 carbon atoms. Specific examples of the alkyl group include linear alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, and octyl; branched alkyl groups such as isopropyl, isobutyl, sec-butyl, and tert-butyl; and cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl. R2 may be an alkyl group in which 80% or more of the hydrogen atoms are substituted with fluorine atoms. Furthermore, R2 may be an alkyl group in which 90% or more of the hydrogen atoms are substituted with fluorine atoms. Furthermore, R2 may be an alkyl group in which 100% or more of the hydrogen atoms are substituted with fluorine atoms. If the hydrogen atoms in the alkyl group are not substituted with fluorine atoms, discoloration occurs after exposure to sunlight or the like.
[0056] By incorporating the aryliodonium salt represented by formula (1), discoloration after exposure to light is suppressed and sufficient pot life under ambient light is ensured. The mechanism behind this is presumed to be as follows, although the present invention is not limited to a specific theory. The introduction of an alkyl group substituted with a fluorine atom increases the hydrophobicity of the aryliodonium salt. This is also true in the excited state, and since the interaction between the aryliodonium salt in the excited state and the polymerization accelerator is reduced, when the aryliodonium salt itself is excited or is in an excited state due to the energy obtained from the photosensitizer, the transfer of energy or electrons to the polymerization accelerator is suppressed, which is presumed to lead to the suppression of discoloration after exposure to sunlight, etc., and the assurance of sufficient pot life under ambient light.
[0057] Particularly preferably, R2 is a straight-chain or branched alkyl group having 1 to 4 carbon atoms in which all of the hydrogen atoms in the alkyl group are substituted with fluorine atoms, and specific examples include CF3, CF3CF2, (CF3)2CF, CF3CF2CF2, CF3CF2CF2CF2, (CF3)2CFCF2, CF3CF2(CF3)CF, and (CF3)3C.
[0058] In formula (1), the number b of R2 is an integer of 1 to 5, preferably 2 to 4, and particularly preferably 2 or 3. The b number of R2 may be the same or different.
[0059] A specific example of a preferred anion moiety is [(CF3CF2)3PF3] - , [(CF3CF2CF2)3PF3] - , [((CF3)2CF)3PF3] - , [((CF3)2CF)2PF4] - , [((CF3)2CFCF2)3PF3] - and [((CF3)2CFCF2)2PF4]-.
[0060] The aryl iodonium salt represented by formula (1) has excellent solubility in polymerizable monomers and polymerization promoting ability, and examples thereof include diphenyl iodonium tris(pentafluoroethyl)trifluorophosphate, ditolyl iodonium tris(pentafluoroethyl)trifluorophosphate, bis(4-dodecylphenyl)iodonium tris(pentafluoroethyl)trifluorophosphate, bis(4-methoxyphenyl)iodonium, (4-octyloxyphenyl)phenyliodonium tris(pentafluoroethyl)trifluorophosphate, bis(4-decyloxy)phenyliodonium tris(pentafluoroethyl)trifluorophosphate, and bis(4-decyloxy)phenyliodonium tris(pentafluoroethyl)trifluorophosphate. iodonium tris(pentafluoroethyl)trifluorophosphate, 4-(2-hydroxytetradecyloxy)phenylphenyliodonium tris(pentafluoroethyl)trifluorophosphate, 4-isopropylphenyl(p-tolyl)iodonium tris(pentafluoroethyl)trifluorophosphate, 4-isobutylphenyl(p-tolyl)iodonium tris(pentafluoroethyl)trifluorophosphate, bis(4-tert-butylphenyl)iodonium tris(pentafluoroethyl)trifluorophosphate and bis(4-tert-butylphenyl)iodonium tris(pentafluoropropyl)trifluorophosphate.
[0061] Usually, the amount of the aryl iodonium salt (c-3) is preferably 0.01 to 10 parts by weight, more preferably 0.05 to 5 parts by weight, or may be, for example, 0.5 to 3 parts by weight, based on 100 parts by weight of the total amount of the polymerizable monomer (a). If the amount of the aryl iodonium salt is less than 0.01 parts by weight, the polymerization promotion ability is poor and curing is insufficient. If more than 10 parts by weight is added, although sufficient curing ability is obtained, the ambient light stability is shortened and discoloration increases, such as the cured body turning brown.
[0062] These photopolymerization initiators can be used alone or in combination of two or more kinds. In addition, these polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules as necessary without any problem. Furthermore, these various types of photopolymerization initiators can be used alone or in combination of two or more kinds, regardless of the polymerization mode or polymerization method.
[0063] The dental photocurable composition of the present invention may contain a chemical polymerization initiator other than the photopolymerization initiator (c), and any known chemical polymerization initiator may be used without limitation. As the chemical polymerization initiator, thiourea derivatives, organic peroxides having a hydroperoxide group, and sulfinates may be used alone or in combination.
[0064] As the thiourea derivative, any known thiourea derivative can be used without limitation. Specific examples of the thiourea derivative include dimethylthiourea, diethylthiourea, tetramethylthiourea, (2-pyridyl)thiourea, N-methylthiourea, ethylenethiourea, N-allylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, N-benzylthiourea, 1,3-dicyclohexylthiourea, N,N'-diphenylthiourea, 1,3-di(p-tolyl)thiourea, 1-methyl-3-phenylthiourea, N-acetylthiourea, N-benzoylthiourea, diphenylthiourea, and dicyclohexylthiourea. Among these, N-acetylthiourea and N-benzoylthiourea may be used. A plurality of these thiourea derivatives may be used in combination as necessary. The amount of the thiourea derivative to be blended is preferably 0.1 to 4 parts by weight based on the total amount of all polymerizable monomers. If it is less than 0.1 part by weight, the polymerization promoting ability is insufficient, and if it exceeds 4 parts by weight, the storage stability may decrease.
[0065] As the organic peroxide having a hydroperoxide group, any known organic peroxide having a hydroperoxide group can be used without limitation. Specific examples of the organic peroxide include t-butyl hydroperoxide, cyclohexyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, and the like. From the viewpoint of reactivity, cumene hydroperoxide may be used. These organic peroxides may be used in combination of a plurality of types as necessary. The amount of the organic peroxide having a hydroperoxide group is preferably 0.1 to 4 parts by weight based on the total amount of all polymerizable monomers. If it is less than 0.1 part by weight, the ability as a polymerization promoter is insufficient, and if it exceeds 4 parts by weight, the storage stability may decrease.
[0066] Examples of the sulfinic acid derivatives include salts (which may be of alkali metals or alkaline earth metals) of p-toluenesulfinic acid, benzenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and the like. Specific examples of the salt compounds of these sulfinic acids include sodium p-toluenesulfinate and sodium benzenesulfinate.
[0067] <(d) Solvent> The (d) solvent that can be used in the present invention can be any known solvent used in the dental field without any restrictions. Representative examples of suitable solvents include water and organic solvents, and among organic solvents, water-soluble volatile organic solvents with a boiling point of 100°C or less under normal pressure are preferred, and specific examples thereof include ethanol, methanol, 1-propanol, isopropyl alcohol, acetone, methyl ethyl ketone, 1,2-dimethoxyethane, 1,2-diethoxyethane, and tetrahydrofuran, and particularly preferred are water, acetone, and ethanol. The amount of the (d) solvent may be 1 to 300 parts by weight, for example, 50 to 300 parts by weight, or 100 to 250 parts by weight, based on the total amount of all polymerizable monomers.
[0068] <Other ingredients> In addition, the dental photocurable composition of the present invention may contain components other than the above components (a) to (d) as long as the effects of the present invention are not impaired. For example, excipients such as fumed silica, benzophenone-based and benzotriazole-based ultraviolet absorbers, polymerization inhibitors such as hydroquinone, hydroquinone monomethyl ether, and 2,5-ditertiary butyl-4-methylphenol, mercaptan compounds such as α-alkylstyrene compounds, n-butyl mercaptan, and n-octyl mercaptan, chain transfer materials such as terpenoid compounds such as limonene, myrcene, α-terpinene, β-terpinene, γ-terpinene, terpinolene, β-pinene, and α-pinene, metal capture materials such as aminocarboxylic acid-based chelating agents and phosphonic acid-based chelating agents, discoloration inhibitors, antibacterial agents, color pigments, water and solvents that can be mixed with water at any ratio, and other conventionally known additives can be added as necessary.
[0069] The method for preparing the dental photocurable composition of the present invention is not particularly limited. A general method for preparing a dental photocurable composition includes a method in which a binder resin is prepared by mixing (a) a polymerizable monomer and (c) a photopolymerization initiator in advance, and then this binder resin is kneaded with (b) a filler, and air bubbles are removed under vacuum to prepare a uniform paste-like composition, and a method in which a polymerizable monomer is mixed with (c) a photopolymerization initiator and (d) a solvent to prepare a uniform liquid composition. In the present invention, the composition can be produced without any problems by the above-mentioned production method. [Industrial Applicability]
[0070] In the dental field, dental photocurable compositions are used for treatment of the oral cavity, and are applied to dental adhesives, dental composite resins, dental abutment construction materials, dental resin cements, dental surface coating materials, dental pit and fissure sealants, dental manicure materials, etc., and therefore have the potential for industrial use. EXAMPLES
[0071] Examples of the present invention will be specifically described below, but the present invention is not limited to these examples.
[0072] The materials used in the examples and comparative examples and their abbreviations are shown below. [(a) Polymerizable monomer] Bis-GMA: 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane 2.6E: 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane having an average molar number of ethoxy groups of 2.6. ·UDMA: N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)ethanol]methacrylate TEGDMA: Triethylene glycol dimethacrylate ·GDMA: Glycerol dimethacrylate 2-HEMA: 2-hydroxyethyl methacrylate MDP: 10-methacryloyloxydecyl dihydrogen phosphate 6-MHPA: 6-Methacryloxyhexylphosphonoacetate 4-MET: 4-methacryloxyethyl trimellitic acid
[0073] [(c) Polymerization initiator] (c-1) Photosensitizer ·CQ: α-camphorquinone
[0074] (c-2) Polymerization accelerator Aromatic tertiary amine compounds DMBE: Ethyl N,N-dimethylaminobenzoate Aliphatic tertiary amine compounds ·DMAEMA: N,N-Dimethylaminoethyl methacrylate organometallic compound SnL: Dioctyl-tin-dilaurate
[0075] (c-3) Diaryliodonium salts IPIFP: 4-isopropylphenyl(p-tolyl)iodonium tris(pentafluoroethyl)trifluorophosphate
[0076] [ka] tBIFP: Bis(4-tert-butylphenyl)iodonium tris(pentafluoropropyl)trifluorophosphate
[0077] [ka] DPIHP: Diphenyliodonium hexafluorophosphate
[0078] (d) Solvent ·water ·acetone
[0079] [(b) Filler] The manufacturing method of each filler used in the preparation of the dental photocurable composition is shown below.
[0080] To 100.0 g of zirconium silicate filler (average particle size 2.2 μm: zirconia 90 wt%, silica 10 wt%), 50.0 g of water, 35.0 g of ethanol, and 3.0 g of 3-methacryloyloxypropyltrimethoxysilane as a silane coupling agent were stirred at room temperature for 2 hours, and the silane coupling treatment liquid obtained was added and stirred for 30 minutes. After that, heat treatment was performed at 140 ° C for 15 hours to obtain filler 1.
[0081] To 100.0 g of zirconium silicate filler (average particle size 0.8 μm: zirconia 85 wt%, silica 15 wt%), 50.0 g of water, 35.0 g of ethanol, and 5.0 g of 3-methacryloyloxypropyltrimethoxysilane as a silane coupling agent were stirred at room temperature for 2 hours, and the silane coupling treatment liquid obtained was added and stirred for 30 minutes. After that, heat treatment was performed at 140 ° C for 15 hours to obtain filler 2.
[0082] Chemical polymerization initiator Thiourea Derivatives BTU: N-benzoylthiourea Organic peroxides containing hydroperoxide groups ·CHP: Cumene hydroperoxide
[0083] UV absorbers BT: 2-(2-hydroxy-5-methylphenyl)benzotriazole Polymerization inhibiting material BHT: 2,6-di-t-butyl-4-methylphenol
[0084] <Method of producing dental photocurable composition (dental filling composite resin)> The polymerizable monomer (a), polymerization initiator (c), and other ingredients shown in Table 1 were mixed for 24 hours at 100 rpm using a mix rotor VMRC-5 to obtain a binder resin in which each ingredient was uniformly dissolved. The binder resin and filler (b) were then added to a kneader, uniformly stirred, and degassed under vacuum to prepare the dental photocurable compositions of Examples 1 to 12 and Comparative Examples 1 and 2.
[0085] [Table 1]
[0086] <Method for producing dental photocurable composition (dental resin cement)> The polymerizable monomer (a), polymerization initiator (c), and other materials shown in Table 2 were mixed for 24 hours at 100 rpm using a mix rotor VMRC-5 to obtain a binder resin in which each material was uniformly dissolved. The binder resin and filler (b) were then placed in a kneader and uniformly stirred, and then degassed under vacuum to obtain pastes 1 and 2. These were then filled into a double syringe (5 mL) manufactured by Mixpack Co., Ltd. to prepare the dental photocurable compositions of Examples 13 to 22 and Comparative Examples 3 to 4.
[0087] [Table 2]
[0088] <Production method of dental photocurable composition> The polymerizable monomer (a), polymerization initiator (c), and other components shown in Table 3 were mixed for 24 hours at 100 rpm using a mix rotor VMRC-5 to prepare dental photocurable compositions of Examples 23 to 28 and Comparative Examples 5 to 8 in which each material was uniformly dissolved.
[0089] [Table 3]
[0090] <Method for producing dental photocurable composition (dental adhesive)> (a) Polymerizable monomer, (c) photopolymerization initiator, and (d) solvent shown in Table 4 were mixed using a Turbula Mixer T2F (Shinmaru Enterprises) to prepare homogeneous liquid dental photocurable compositions, which were then filled into light-shielding plastic containers to prepare the dental photocurable compositions of Examples 29 to 36 and Comparative Examples 9 to 10.
[0091] [Table 4]
[0092] The test methods used in the examples and comparative examples are as follows. The dental filling composite resin and dental resin composition were directly collected, and the dental resin cement was prepared by mixing paste 1 and paste 2 using a mixing tip manufactured by Mixpack.
[0093] (1) Bending strength The dental photocurable composition thus prepared was filled into a stainless steel mold, cover glass was placed on both sides, and the composition was pressed against a glass plate. Then, light was irradiated at 5 locations for 10 seconds each using a photopolymerization irradiator (Blue Shot, manufactured by Matsukaze) to cure the composition. After curing, the cured product was removed from the mold, and the back side was irradiated with light in the same manner to obtain a test specimen (25×2×2mm: rectangular parallelepiped type). The test specimen was immersed in water at 37°C for 24 hours, and then a bending test was performed. The bending test was carried out using an Instron universal testing machine (manufactured by Instron Corporation) with a support distance of 20 mm and a crosshead speed of 1 mm / min.
[0094] (2) Environmental light stability Using a light meter, the height of a dental lamp (Luna-Vue S, Morita Seisakusho) was adjusted so that light with an illuminance of 8000±1000 lx hit the sample mounting area. A glass slide (26×16 mm, 2 mm thick) was placed on a glass mixing board covered with non-glossy black paper, and approximately 30 mg of sample was taken on it. After the sample was exposed to light for 60±5 seconds on the sample mounting area, it was removed from the sample mounting area and another glass slide was immediately pressed against the sample to form a thin layer. If the state of the sample at this time was not physically uniform, it was determined that curing had begun, and the time until curing was evaluated in 5-second increments. The longer this time, the better the environmental light stability.
[0095] (3) Discoloration of the cured product a) Dental photocurable compositions (excluding dental adhesives) The dental photocurable compositions thus prepared were filled into stainless steel molds (15φ×1mm: disk-shaped), and then a cover glass was placed on top and pressed with a glass plate. The cover glass was irradiated with light for 1 minute using a photopolymerization irradiator (Grip Light II: Matsukaze Co., Ltd.) to cure the composition. The cured product was removed from the mold, the cover glass was removed, and the color tone of the test specimen was measured. The color measurement was performed by placing the test specimen on a background of a standard white board (D65 / 10°X=81.07, Y=86.15, Z=93.38) and using a spectrophotometer (manufactured by BYK-Chemie) under a set of predetermined conditions (light source: C, viewing angle: 2°, measurement area: 11mm). After that, the test specimen was exposed to light for 24 hours using a xenon lamp light exposure tester (Suntest CPS+), and the color tone of the test specimen was measured again, and the difference in color change was expressed as ΔE calculated from the following formula. ΔE={(ΔL*) 2 +(Δa*) 2 +(Δb*) 2} 1 / 2 ΔL*=L1*-L2* Δa*=a1*-a2* Δb*=b1*-b2* Here, L1* is the lightness index before light exposure, L2* is the lightness index after light exposure, a1* and b1* are color quality indices before light exposure, and a2* and b2* are color quality indices after light exposure. b) Dental photocurable composition (dental adhesive) A polyethylene frame with a thickness of 50 μm was fixed on a glass plate, the prepared dental photocurable composition was applied inside the frame, and the air drying was repeated until the liquid surface stopped moving. When the thickness reached 50 μm or more, the glass plate was pressed against the plate and cured by irradiating light for 1 minute using a photopolymerization irradiator (Grip Light II: manufactured by Matsukaze). After removing the cured product from the frame, the cover glass was removed, and the color tone of the test specimen was measured. The color measurement was performed by placing the test specimen on a background of a standard white plate (D65 / 10°X=81.07, Y=86.15, Z=93.38) and using a spectrophotometer (manufactured by BYK-Chemie) under a certain set of conditions (light source: C, viewing angle: 2°, measurement area: 11 mm). After that, the test specimen was immersed in water at 37°C for 2 months, and the color tone of the test specimen was measured again, and the difference in color change was expressed as ΔE calculated from the following formula. ΔE={(ΔL*) 2 +(Δa*) 2 +(Δb*) 2} 1 / 2 ΔL*=L1*-L2* Δa*=a1*-a2* Δb*=b1*-b2* Here, L1* is the lightness index before immersion, L2* is the lightness index after immersion, a1* and b1* are color quality indices before immersion, and a2* and b2* are color quality indices after immersion.
[0096] (4) Evaluation of storage stability The prepared dental photocurable composition was stored in a thermostatic chamber set at 50°C under cover, and after 90 days, (3) the same test for discoloration of the cured product was performed to check for precipitation of the aryl iodonium salt. Storage stability was evaluated based on the change over time between the initial value and the value after 90 days at 50°C. Regarding precipitation, the paste was discharged from the syringe and the presence or absence of precipitation was checked. Those with no precipitation at all were rated A, those with slight precipitation were rated B, and those with obvious precipitation were rated C. In addition, dental photocurable compositions without the aryl iodonium salt were prepared as reference samples for each composition, and it was confirmed that none of them had any precipitation.
[0097] (5) Evaluation of durable adhesive strength The crown of the extracted mandibular permanent central incisor was cut and the tooth fragment was embedded in epoxy resin. The embedded tooth was exposed to the dentin with #600 waterproof abrasive paper under water, washed with water, and dried. A double-sided tape with a hole of 4 mm in diameter is applied to the exposed dentin to define the adhesive surface. A plastic mold (inner diameter 4 mm, height 2 mm or 4 mm) is fixed to the defined surface, and a dental hardenable composition is applied to the adhesive surface, and the composition is cured by irradiating light for 20 seconds using a photopolymerization irradiator (Grip Light II: manufactured by Matsufu). The dental composite resin "Beauty Fill Flow Plus" (Matsufu Co., Ltd.) is then filled into the mold, and the composition is cured by irradiating light for 20 seconds again. The plastic mold is removed to prepare an adhesive test specimen. The adhesive test specimen is immersed in distilled water at 37°C for 24 hours, and then a dentin adhesion test is performed using an Instron universal testing machine (Instron 5567, manufactured by Instron) at a crosshead speed of 1 mm / min, based on shear adhesive strength, to measure the initial adhesive strength. In addition, adhesive test specimens were prepared and immersed in distilled water at 37°C for 24 hours, after which they were subjected to 10,000 thermal cycles (alternate immersion at 55°C for 30 seconds and 5°C for 30 seconds) and a dentin adhesion test was conducted, with the results being regarded as durable adhesive strength.
[0098] [Examples 1 to 12] The dental photocurable compositions of Examples 1 to 12 exhibited high bending strength, excellent environmental light stability, and high discoloration resistance. Furthermore, almost no decrease in discoloration resistance or precipitation was observed even after 90 days at 50°C, demonstrating excellent storage stability.
[0099] [Comparative Examples 1-2] The dental photocurable composition of Comparative Example 1 had low stability to ambient light, and was significantly discolored, and precipitation of aryl iodonium salts was observed. The dental photocurable composition of Comparative Example 2 was confirmed to have low bending strength and significant discoloration.
[0100] Table 5 shows the evaluation results for the dental photocurable compositions (dental resin cements) of the Examples and Comparative Examples.
[0101] [Table 5] [Examples 13 to 22] The dental photocurable compositions of Examples 13 to 22 exhibited high bending strength, excellent stability to environmental light, and high resistance to discoloration. Even after 90 days at 50°C, almost no decrease in resistance to discoloration or precipitation was observed, and the compositions had excellent storage stability.
[0102] [Comparative Examples 3 to 4] The dental photocurable composition of Comparative Example 3 showed significant discoloration and precipitation of aryl iodonium salt was observed. It was confirmed that the dental photocurable composition of Comparative Example 4 had low bending strength and significant discoloration.
[0103] Table 6 shows the evaluation results for the dental photocurable compositions of the Examples and Comparative Examples.
[0104] [Table 6] [Examples 23 to 28] The dental photocurable compositions of Examples 23 to 28 exhibited high bending strength and excellent environmental light stability, and no precipitation of the aryliodonium salt was observed even after 90 days at 50° C., demonstrating excellent storage stability.
[0105] [Comparative Examples 5 to 8] The dental photocurable compositions of Comparative Examples 5 and 6 had low bending strength and low environmental light stability, and precipitation of aryl iodonium salts was observed after 90 days at 50° C. The dental photocurable compositions of Comparative Examples 7 and 8 had low bending strength, and Comparative Example 8 was also confirmed to have low environmental light stability.
[0106] [Table 7] In Table 7, "-" indicates that no aryliodonium salt is included.
[0107] [Examples 29 to 36] The dental photocurable compositions of Examples 29 to 36 had high adhesive strength, particularly high durable adhesion, and no precipitation of aryliodonium salt was observed even after 90 days at 50°C. Discoloration after immersion in water was extremely low, indicating excellent storage stability.
[0108] [Comparative Examples 9 and 10] The dental light-curable compositions of Comparative Examples 9 and 10 had low adhesive strength and color stability, and precipitation of the aryl iodonium salt was observed after 90 days at 50° C. These results demonstrated the effectiveness of the aryl iodonium salt with a specific structure.
[0109] [Table 8]
[0110] In the above examples, a dental filling composite resin, a dental resin cement, and a dental adhesive have been described, but the present invention can be used for other dental photocurable compositions without any restrictions.
Claims
1. In the photopolymerization initiator (c) used in the dental photocurable composition, (c-1) a photosensitizer, (c-2) a polymerization accelerator, and (c-3) Formula (1): 【Chemistry 1】 (wherein R1 represents an organic group bonded to I, R2 represents an alkyl group in which some of the hydrogen atoms are substituted with fluorine atoms, and b represents the number of alkyl groups and is an integer of 1 to 5). A photopolymerization initiator comprising:
2. The photopolymerization initiator according to claim 1, wherein the formula (1) of (c-3) is an aryl iodonium salt in which R2 is an alkyl group in which 80% or more of the hydrogen atoms are substituted with fluorine atoms.
3. (c) the photopolymerization initiator according to claim 1, and (a) Polymerizable monomer A dental photocurable composition comprising:
4. (c) the photopolymerization initiator according to claim 1; (a) a polymerizable monomer, and (b) Filler material A dental photocurable composition comprising:
5. (a) relative to 100 parts by mass of the polymerizable monomer, (c-1) photosensitizer: 0.1 to 5 parts by mass, (c-2) a polymerization accelerator: 0.01 to 10 parts by mass, and (c-3) an aryl iodonium salt represented by formula (1): 0.01 to 10 parts by mass, 5. The dental photocurable composition according to claim 1, further comprising (c) a photopolymerization initiator.
6. (a) relative to 100 parts by mass of the polymerizable monomer, (b) 10 to 1,900 parts by weight of a filler The dental photocurable composition according to claim 5 , which comprises
7. 7. The dental photocurable composition according to any one of claims 3 to 6, which is a dental adhesive, a dental composite resin, a dental abutment construction material, a dental resin cement, a dental surface coating material, a dental pit and fissure sealant, or a dental manicure material.
Citation Information
Patent Citations
Photopolymerization initiator composition and photopolymerization composition
JP2004196949A
Photosetting composite restoration material for dental use
JP2005213231A
Curable material kit for dental treatment
JP2009051826A
Energy ray-curable composition containing iodonium alkyl fluorophosphate-based photoacid generator
JP2012022227A
Fluorinated alkyl phosphoric onium salt-based acid generator
JP2012246456A